Avaliação clínica e histológica do efeito cicatricial da pomada colagenase e da pomada colagenase e cloranfenicol mucosa do palato de ratos Wistar - Oliveira, Letícia Freitas De (2018)
Gingival grafts consist of surgical removal of tissues from donating areas and the replacement of them on gingival recessions. The palatine mucosa is the main donating source of conjunctive and epithelium tissue, due to it being coated by a keratin layer. The graft removal area is anatomically located between the last palatine roughness and the area of the foramen palatine major (from the first premolar to the second molar). Nowadays the gingival grafts have been widely used to solve periodontal esthetical problems. The objective of this study is the clinical and histological evaluation of the action of the colagenase, and colagenase and cloranfenicol creams in the process of repairing the tissues of a wound on the palate mucosa of mousses. A wound in the mousse’s palate was done and the application of the respective materials was carried out, vaseline on the negative control Group I. Group II received an application of colagenase while Group III received colagenase and cloranfenicol and Group IV cloranfenicol, all of the applications were done once a day for 3 days. On the first, fifth, seventh and tenth day after the treatment, three animals from each group were euthanized. Posteriorly the clinical and histological analysis of the tissue repair on the wound was performed and the physiological parameters evaluation AST and ALT. The study shows that the drugs used didn’t intervene negatively in the process of tissue repair. The results showed that there was not any statistic difference in the measures of the wo und after treatment and that the biochemical parameters presented values statistically equivalent.